2006
DOI: 10.1063/1.2358826
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic properties of the MnGa2Se4 compound under high pressure

Abstract: International audienceX-ray diffraction measurements on MnGa2Se4, a II-III2-VI4 magnetic semiconductor compound, are made as a function of pressure up to 25 GPa. It is found that in the range of 0P12 GPa the structure is a defect tetragonal; in the range between 12 and 14 GPa a two phase field +NaCl type exists. It is found that at about 14 GPa a transition to the cubic NaCl-type structure occurs and it appeared that this transition is irreversible. From the analysis of the x-ray diffraction lines, lattice par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 19 publications
11
24
0
Order By: Relevance
“…At 12.5 GPa, the new peaks fully develop and the peaks of the low-pressure phase cannot be detected anymore. As found in ZnGa 2 Se 4 and related compounds, [8][9][10][11][12][13] we found that the XRD patterns of the HP structure of ZnGa 2 Te 4 can be assigned to a cubic rocksalt-type structure ðFm 3mÞ, where the Te atoms are located at the 4b site, while the Zn and Ga atoms are located at the 4a sites with a partial SOF. Results of the Rietveld refinements indicating the good match of this disordered rocksalt-type (DR) structure with the experimental results are shown in Fig.…”
Section: B Pressure-induced Phase Transitionsmentioning
confidence: 80%
See 2 more Smart Citations
“…At 12.5 GPa, the new peaks fully develop and the peaks of the low-pressure phase cannot be detected anymore. As found in ZnGa 2 Se 4 and related compounds, [8][9][10][11][12][13] we found that the XRD patterns of the HP structure of ZnGa 2 Te 4 can be assigned to a cubic rocksalt-type structure ðFm 3mÞ, where the Te atoms are located at the 4b site, while the Zn and Ga atoms are located at the 4a sites with a partial SOF. Results of the Rietveld refinements indicating the good match of this disordered rocksalt-type (DR) structure with the experimental results are shown in Fig.…”
Section: B Pressure-induced Phase Transitionsmentioning
confidence: 80%
“…Details of the structural model are given in Table II. We would like to stress here, that in spite the DR structure was previously assigned to the HP phase of other members of the AB 2 X 4 family, [8][9][10][11][12][13] this is the first time that it is assigned using enough Bragg peaks (fourteen) to be confident on the structural assignment. This was possible thanks to the large unit-cell volume of ZnGa 2 Te 4 and the large angular aperture of the DAC used in the experiments (2h < 25 ).…”
Section: B Pressure-induced Phase Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work is devoted to the investigation of the structural and vibrational behaviour of this OVC under high pressure at room temperature. Tuning the thermodynamic variable pressure, we envisage to transform the initial ordered PS phase into a disordered cationic structure, which could be recovered at ambient conditions after compression, as observed in some previous studies on OVC materials 9,[15][16][17][18]23 . In situ angle-dispersive XRD and…”
Section: Ternary Adamantinementioning
confidence: 99%
“…High‐pressure studies of OVCs with A II B 2 III X 4 VI stoichiometry are receiving increasing attention in the last years . The vast majority of these works have been focused on the study of the structural and vibrational properties of A II B 2 III X 4 VI compounds by means of X‐ray diffraction (XRD) and Raman scattering (RS) measurements, respectively.…”
Section: Introductionmentioning
confidence: 99%